Singular perturbation problems for time-reversible systems - Buzzi, C. A.; Da Silva, P. R.; Teixeira, M. A. (Amer Mathematical Soc, 2005)
In this paper singularly perturbed reversible vector fields defined in R-n without normal hyperbolicity conditions are discussed. The main results give conditions for the existence of infinitely many periodic orbits and heteroclinic cycles converging to singular orbits with respect to the Hausdorff distance.
Keywords: singular perturbations; time-reversible systems